Força muscular de membros inferiores, índice BODE, equilíbrio e capacidade funcional em pacientes com doença pulmonar obstrutiva crônica em reabilitação pulmonar - Santos, Júlia Gianjoppe dos (2013)
Background: Decreased peripheral muscle strength is associated with the limitation of functional capacity, however there is not sufficient evidences showing direct impact of peripheral muscle weakness on balance tasks and functional mobility, as well as the prognosis of mortality in patients with chronic obstructive pulmonary disease (COPD). Objectives: The objectives of the study was to assess the relationship of the peripheral muscle strength with BODE index, functional capacity and balance and functional mobility in patients with COPD in pulmonary rehabilitation (PR) and investigate if these patients present muscle weakness, being able to influence the balance and the prognosis of mortality. Methods: It is a cross-sectional study which evaluated 24 patients (age>50 years) of both genders, with moderate to very severe obstruction (FEV1=44(31 - 62,8)%predicted). Patients underwent the following evaluations: modified Medical Research Council (mMRC), Six-minute Walk Test (6MWT), BODE index, Timed Test "Up and Go" (TUG), Berg Balance Scale (BBS), Dynamic Gait Index (DGI), Muscle Strength Test in Knee Extensors (KExt) and Hip Abductors (HAbd) with dynamometer MicroFet2. Results: We found significant correlations of peripheral muscle strength with BODE index (KExt = -0.45; HAbd= -0.58) and mMRC (KExt = -0.48; HAbd = -0.49). In this sample, 54% of patients had muscle weakness in ExtJ and there were and there were differences for 6MWT and mMRC among patients with normal or decreased knee extensor strength, however there were no differences for BMI, FEV1, BODE Index, TUG, BBS and DGI. Conclusions: The isometric muscular strength of lower limbs is associated with the prognosis of mortality and dyspnea in patients with COPD, even being submitted to PR. Although the strength of the lower limbs present negative impact on functional capacity and dyspnea, patients with COPD on PR tend to keep preserved balance and functional mobility.